Evaluation of pain management and contributing factors in clients of the "Pain Relief and Palliative Care Polyclinic", Herminda Martin Hospital, Chile - Gloria Araneda Pagliotti; Héctor Acuña Ortiz; Claudia Gutiérrez Cádiz; Marcelo Troncoso Véjar; Fernanda Zañartu Gaete (Universidad de Alicante, 2012)
Descriptive study whose aim was to identify pain management and evolution considering some contributing factors in adult and eider clients attending the Pain relief and palliative care Polyclinic at Herminda Martin Hospital, Chile. A sample of 59 both male and female clients in easily accesible urban or rural areas were asked to answer a 29 item questionnaire during a home visit, whether they knew their diagnose or not. This questionnaire included the Scott-Huskinsson visual scale for pain and the WHO analgesic scale for classification of pharmacological treatment. The results obtained showed that 64.4% of the sample did not complain of pain at the time, 49.2% is 66 years or older, 59.3% are female, 84.7% live in urban areas, 91.5% went to school, 88.1% are in benefit range A and B, 52.5% have a partner, the same percentage does not know their diagnose and 52.9% have taken opioids for 1 to 4 months. Statistically significant variables were the utilization and type of opioid for pain management. Sociodemographic factors did not present significant statistical correlation.